Transmission of monkeypox/mpox virus: A narrative review of environmental, viral, host, and population factors in relation to the 2022 international outbreak. Issue 2 (6th February 2023) - Pan, Daniel; Nazareth, Joshua; Sze, Shirley; Martin, Christopher A.; Decker, Jonathan; Fletcher, Eve; Déirdre Hollingsworth, T.; Barer, Michael R.; Pareek, Manish; Tang, Julian W.
Abstract: Monkeypox virus (MPXV) has spread globally. Emerging studies have now provided evidence regarding MPXV transmission, that can inform rational evidence‐based policies and reduce misinformation on this topic. We aimed to review the evidence on transmission of the virus. Real‐world studies have isolated viable viruses from high‐touch surfaces for as long as 15 days. Strong evidence suggests that the current circulating monkeypox (mpox) has evolved from previous outbreaks outside of Africa, but it is yet unknown whether these mutations may lead to an inherently increased infectivity of the virus. Strong evidence also suggests that the main route of current MPXV transmission is sexual; through either close contact or directly, with detection of culturable virus in saliva, nasopharynx, and sperm for prolonged periods and the presence of rashes mainly in genital areas. The milder clinical presentations and the potential presence of presymptomatic transmission in the current circulating variant compared to previous clades, as well as the dominance of spread amongst men who have sex with men (MSMs) suggests that mpox has a developed distinct clinical phenotype that has increased its transmissibility. Increased public awareness of MPXV transmission modalities may lead to earlier detection of the spillover of new cases into other groups.